2013
DOI: 10.1093/brain/awt025
|View full text |Cite
|
Sign up to set email alerts
|

Side population in human glioblastoma is non-tumorigenic and characterizes brain endothelial cells

Abstract: The identification and significance of cancer stem-like cells in malignant gliomas remains controversial. It has been proposed that cancer stem-like cells display increased drug resistance, through the expression of ATP-binding cassette transporters that detoxify cells by effluxing exogenous compounds. Here, we investigated the ‘side population’ phenotype based on efflux properties of ATP-binding cassette transporters in freshly isolated human glioblastoma samples and intracranial xenografts derived thereof. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 46 publications
5
88
0
1
Order By: Relevance
“…Using flow cytometric analysis, we found that CD31 positive cells in the tumour were GFP-positive and thus host-derived, and displayed strong efflux properties (so-called ‘side population’ (SP) phenotype), a hallmark of brain ECs (Figure 3C, Suppl. Figure 3A-3B) [16]. Although by flow cytometry a CD31 signal was occasionally (0-0.4%) detected within tumour cells (black, Figure 3C), the signal intensity was close to background and was far from the CD31 expression level (up to 100 fold lower) typically seen in human ECs or HBMVEC cells (Suppl.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using flow cytometric analysis, we found that CD31 positive cells in the tumour were GFP-positive and thus host-derived, and displayed strong efflux properties (so-called ‘side population’ (SP) phenotype), a hallmark of brain ECs (Figure 3C, Suppl. Figure 3A-3B) [16]. Although by flow cytometry a CD31 signal was occasionally (0-0.4%) detected within tumour cells (black, Figure 3C), the signal intensity was close to background and was far from the CD31 expression level (up to 100 fold lower) typically seen in human ECs or HBMVEC cells (Suppl.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that glioblastomas mostly comprise ECs, pericytes, microglia/macrophages and neural stem cells [16]. Because ECs constitute a major population of the glioma microenvironment and are the mediators of the angiogenic process, we focused on the interaction of tumour cells with ECs.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach to CSC enrichment is the use of flow cytometry to isolate a side population containing CSCs, which is based on the hypothesis that stem cells contain drug efflux transporters (Yu et al 2008). While this approach has identified a population of self-renewing cells in a mouse glioma model (Bleau et al 2009), it has not been used successfully to enrich for self-renewing cells in human GBM (Broadley et al 2011;Golebiewska et al 2013), highlighting the model-and species-specific challenges of enrichment methods.…”
Section: Csc Enrichmentmentioning
confidence: 99%
“…GSCs express the ATP-binding cassette (ABC) transporter channels at an increased rate compared to differentiated tumor cells, adding to the known challenges in drug delivery presented by the BBB and irregular tumor vasculature [26,70]. ABC channels actively and expeditiously transport molecules, including TMZ, both at the BBB and the cellular level to allow some cells to completely elude therapy and promote recurrence [52,71]. Expression of these proteins, with ABCG2 being the main example, is also associated with subpopulations of cells that are stem-like and multidrug resistant [26].…”
Section: Molecular Mechanisms Of Glioma Stem Cell Resistance To Chmentioning
confidence: 99%